2020
DOI: 10.1177/1403494820930952
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence, associations with perceived need for help and health care utilization: a population-based sample of women in Sweden

Abstract: Aim: To assess the association between physical intimate partner violence (physical IPV) in the past 5 years, perceived need for help and primary health care utilization due to mental health problems in a general population-based sample of women in Sweden. Methods: We performed structured follow-up interviews with 616 women between 1995 and 2015. Associations between physical IPV in the past 5 years and (i) perceived need for help and (ii) primary health care utilization due to mental health problems, were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…IPV has devastating effects on women's mental health. Women experiencing IPV are at risk for psychological trauma such as anxiety, depression, anxiety, and suicide (13). Evidence shows that many psychological problems women face in society directly result from IPV (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPV has devastating effects on women's mental health. Women experiencing IPV are at risk for psychological trauma such as anxiety, depression, anxiety, and suicide (13). Evidence shows that many psychological problems women face in society directly result from IPV (11).…”
Section: Introductionmentioning
confidence: 99%
“…Women with IPV experience face many barriers to health care, such as financial pressure, instilling fear and control over their husbands, fear of being blamed, and feeling ashamed, and many women who seek treatment never experience IPV (13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these adverse outcomes related to IPV, previous research has shown that help-seeking among survivors is low in most countries. Some never seek help, and those who do mainly choose informal sources of help, usually from their family or friends and are less likely to seek formal help, such as from shelters, healthcare services, or the police [ 22 , 23 , 24 , 25 ]. It should be noted that a significant body of literature suggests that women with a history of IPV use healthcare services more than non-abused women, especially primary care and emergency departments [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high rates of adverse health outcomes, studies have shown that help-seeking among IPV survivors is low. Many survivors never disclose the violence to anyone, and those who do most often choose support from friends and family and are substantially less likely to seek help from formal sources, such as healthcare and social services, even despite their perceived need for such support [ 3 , 9 , 10 , 11 ]. These findings may reflect the limited availability or accessibility of services for abused women in some countries.…”
Section: Introductionmentioning
confidence: 99%